Anti-competitive impact of pseudo-generics - Rodrigues, Vasco (2014)
In pharmaceuticals markets, sellers of branded drugs sometimes sell generic versions of their own branded products, either directly or through licenseagreements. Although claims that these pseudo-generics may have anti-competitive effects are not unusual, the theoretical literature on this issue is limited and not conclusive. This paper uses a model that combines horizontal and vertical product differentiation, to explain how those effects may occur. We show that the producer of the branded product will not sell the pseudo-generic unless faced with competition and that, if she does so, in some circumstances, all prices rise to the benefit of all sellers and the detriment of consumers.